1993
DOI: 10.1159/000187290
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Changes in Ultra Long-Distance Marathon Runners

Abstract: The urine of 45 athletes, male and female, were studied after completing an ultra long-distance marathon race. Of these athletes, 24.4% were found on screening to have red blood cells in the urine. The urinary mean corpuscular volume (MCV) of red cells was used in an attempt to differentiate between lower and upper urinary tract haematuria. With the exception of 1 athlete, the red cells were not dysmorphic and had an MCV greater than 72 fl. This suggested that the haematuria had an origin from the lower urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…As per our knowledge this is the first study where the excretion of blood cells were studied in triathletes. In the consulted literature, this exercise effect is transient and is not associated with pathologies, once it was detected just after physical effort (Poortmans 1984, Irving et al 1986, Kallmeyer and Miller 1993, Bellinghieri et al 2008.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As per our knowledge this is the first study where the excretion of blood cells were studied in triathletes. In the consulted literature, this exercise effect is transient and is not associated with pathologies, once it was detected just after physical effort (Poortmans 1984, Irving et al 1986, Kallmeyer and Miller 1993, Bellinghieri et al 2008.…”
Section: Discussionmentioning
confidence: 97%
“…As in the previous study, the observed exercise effect was attributed to kidney damage, a very unusual event in cyclists. Unlike the study cited above, the occurrence of red blood cells in urine seems to be very common in long distance runners (Ducloux et al 1999, Kallmeyer andMiller 1993). Similar to hematuria, the presence of leucocytes in urine can indicate glomerular or tubular damage, increased glomerular permeability or inflammation of the urinary tract (Poortmans 1984, Ducloux et al 1999) and very few studies have been dedicated to investigate the presence of leucocytes in urine due to physical exertion (Richter et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, there is a toxic effect of hemoglobin in the tubular cells, described as a mechanism responsible by the acute kidney failure in the IgA nephropathy cases with glomerular bleeding (Fogazzi et al, 1995). Despite the clinical condition installed after the strenuous exertion, the exercise effect is transient and is not associated with any pathology (Bellinghieri et al, 2008;Irving, Noakes, Irving, & Van Zyl-Smit, 1986;Kallmeyer & Miller 1993, Poortmans, 1984.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of 12% hematuria after the run seen in our study is more in tandem with that found in Israeli Air Force recruits (5%), 1 unlike the incidence of470% seen in hard core athletes like ultra marathoners, 3 long distance skiers or 45% in professional athletes. [9][10][11][12][13][14] All investigators have commented that post exertional hematuria subsides within 72 h. [2][3][4]12,16,18 However, 19% of our subjects had persistence of hematuria beyond 72 h, and three individuals continued to have hematuria beyond 14 days. On evaluation, they were found to have primary glomerular disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In 1910, Barach 5 reported proteinuria, granular casts and hematuria in marathon runners, which was later labeled as ''athletic pseudonephritis''. 6 Thereafter, many investigators have tried to localize the source of this transient exertional hematuria and proteinuria.…”
Section: Introductionmentioning
confidence: 99%